IMPLEMENTASI PENDIDIKAN KARAKTER UNTUK MENANAMKAN KEPEDULIAN PADA LINGKUNGAN DI SEKOLAH DASAR - Putri Endang Pata Sari; Badruli Martati; Kunti Dian Ayu Afiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of character education for environmental care in SD Negeri 01 Paciran. This study uses a qualitative approach with observation, interview, and documentation methods to collect data on students' habits in maintaining cleanliness, sorting waste, and caring for the environment. The results of the study show that students have implemented environmental care habits through programs such as class pickets, Clean Fridays, and school greening. In addition, the support from teachers, principals, and parents has played an important role in the success of this program. The conclusion of this study confirms that character education for environmental care is effective in forming a generation that is responsible for environmental cleanliness and sustainability from an early age.